Prevalence of gingivitis and periodontitis in an adult male population in Nigeria - Umoh, Agnes; Azodo, Clement (Nigerian Journal of Basic and Clinical Sciences, 2026)
Objective: To determine the prevalence of gingivitis and periodontitis among an adult male population in Benin City, Nigeria.Materials and Methods: The drivers of a private motor transport company whose head office is in Benin City constituted the study participants. Data collection was through an interview-administered questionnaire and periodontal examination. Periodontal disease was assessed using community periodontal index while demographic characteristics, social habits and oral hygiene habits were elicited using interview-administered questionnaire.Results: The prevalence of gingivitis and periodontitis was 75.4% and 15.4% respectively. The prevalence of periodontitis was higher among older participants, those of lower educational attainment and longer driving experience, those that indulged in only once-daily teeth cleaning, tobacco users, regular alcohol and kolanut consumers.Conclusion: The prevalence of gingivitis and periodontitis in this study was similar to previous reports in Nigeria. The prevalence was higher in relation to the risk factors considered in this study thereby necessitating the need for an awareness campaign to enlighten the public about the harmful effects of tobacco, kolanut and alcohol on periodontal health. This study is also recommended among a larger number of people.
Keywords: Drivers; gingivitis; male; periodontal disease; periodontitis